Exploring Literary Devices in The Weary Blues by Langston Hughes for Enhanced Reader Comprehension and Appreciation - Orun, Putri Anugraheli Ramba (Har Press Indonesia, 2024)
This study uses a qualitative approach that focuses on an in-depth analysis of Langston Hughes' poem The Weary Blues, with the aim of exploring and understanding the use of literary devices in the work. The main analytical framework used is L.G. Alexander's theory, which classifies literary devices into three main categories: structural devices, sound devices, and sense devices. The main methodology applied in this study is the close reading technique, which enables in-depth identification and analysis of the various literary devices used by Hughes. In addition, the analysis takes into account the historical and cultural background of the Harlem Renaissance era, which greatly influenced Hughes' works. The primary source of this research is the thoroughly analyzed text of the poem The Weary Blues, as well as various secondary sources that discuss Hughes' work and African-American modernist poetry. The research also integrates aspects of reader response theory to understand how the literary devices used by Hughes influence readers' interpretation and appreciation of his poetry. The results of the analysis show that the use of complex and interrelated literary devices, such as repetition, rhyme, and imagery, enriches the reader's multisensory experience, thereby enhancing understanding and appreciation of the poem. The findings emphasize the importance of more effective educational approaches to teaching poetry analysis as well as learning strategies that can deepen readers' engagement with literary texts.